2017
DOI: 10.1016/j.rppnen.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dose–response relationship between smoking load and cardiopulmonary fitness in adult smokers: A cross-sectional study

Abstract: There appears to be no dose-response relationship between SL and cardiopulmonary fitness in adult smokers with preserved pulmonary function, after adjusting the analysis for age and cardiovascular risk. Our results suggest that smoking cessation might be useful as the primary strategy to prevent cardiopulmonary fitness decline in smokers, regardless of smoking load. Thus, even a very low dose of tobacco use must be avoided in preventive strategies focusing on becoming people more physically active and fit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Other metabolic derangements with a potential to impact on physical performance include: An appreciable (10%) increase in energy expenditure at rest compared to nonsmoking subjects (Hofstetter et al, 1986), impaired sarcoplasmic reticulum Ca ++ uptake in myofibres (Nogueira et al, 2018), and impaired insulin-dependent glycogen recovery from exercise (Jensen et al, 1995). An early lactate threshold might be the final consequence of these bioenergetic derangements in association with chronically low levels of muscle activation, i.e., sedentarism (Miyatake et al, 2011; Lauria et al, 2017).…”
Section: Peripheral Muscular Abnormalitiesmentioning
confidence: 99%
“…Other metabolic derangements with a potential to impact on physical performance include: An appreciable (10%) increase in energy expenditure at rest compared to nonsmoking subjects (Hofstetter et al, 1986), impaired sarcoplasmic reticulum Ca ++ uptake in myofibres (Nogueira et al, 2018), and impaired insulin-dependent glycogen recovery from exercise (Jensen et al, 1995). An early lactate threshold might be the final consequence of these bioenergetic derangements in association with chronically low levels of muscle activation, i.e., sedentarism (Miyatake et al, 2011; Lauria et al, 2017).…”
Section: Peripheral Muscular Abnormalitiesmentioning
confidence: 99%
“…Borba et al 18 found a similar statistically significant reduction in VO 2 /kg in current and second-hand smokers compared to non-smokers. In another study found similar results and showed that in smokers, cardiorespiratory fitness is reduced regardless of the smoking load, thus is possible that the cessation of smoking can be used to prevent the reduction of cardiorespiratory fitness 19 . Additionally, in the same study the smoking was also related to other cardiovascular risk factors 19 .…”
Section: Discussionmentioning
confidence: 55%
“…Fourth, despite our efforts to appropriately match the PAD + CAD group with the two control groups, these patients still had a significantly higher prevalence of smoking, a factor which might have affected our results. Nevertheless, the magnitude of difference in oxygen consumption, oxygen pulse [ 40 , 41 , 42 ] and certainly in diastolic dysfunction and chronotropic incompetence cannot be attributed to smoking alone.…”
Section: Discussionmentioning
confidence: 99%